The monkey's paw - Jacobs, W. W. (William Wymark), 1863-1943. (Logan, Iowa : Perfection Learning Corp., 1979)
W.W. Jacobs' short story in which a mummified monkey's paw carrying a spell receives three wishes from a family and proceeds to fulfill them in unexpected and horrible ways. Includes reading and writing exercises.
"British literature"--Front cover.
"#97278"--Back cover.
Young Adult
Young Adult
420
Keywords: Wishes -- Fiction; Wishes -- Fiction; Horror fiction; Horror fiction